CLASSROOM OBSERVATION AND RESEARCH - Dhion Meitreya Vidhiasi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2018)
There are so many methods that can be used in conducting research. Every method has its own strength and weakness. Before a researcher conduct research, they must choose which method or techniques are more appropriate. This paper explains that there are at least for methods that can be used when a researcher wants to conduct research in teaching and learning development. Those methods are a formal experiments, stimulated recall, observation schemes, and interaction analysis. The focus of this paper is not about how the method is but how researchers observe what is going on inside the classroom using those methods.